Hot embossing of micro devices - Yang, Yong Lin (2011)
In today industrial, Micro-Electro-Mechanical Systems (MEMS) technology is commonly used. For commercialization of this technology, the 2 main criteria are low cost fabrication and also high volume production. Due to these 2 reasons, in recent years, there is a shift of products from silicon based material to polymer based material. For the production of polymer based products, there is an increasing interest in hot embossing manufacturing process. In this project, a systematic way of optimizing the process parameters will be discussed. The polymeric substrate will be embossed with steel-machined mold insert and replication quality will be inspected using Scanning Electron Microscope.